KOORDINASI DALAM MENGATASI ANGKUTAN ILEGAL DI PROVINSI RIAU - Hotnika Simanjuntak; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the fundamental problems in Riau Province government is the transportation, especially in the tackle illegal transportation, where every year is grow more and more difficult. As for instance the authorities in handling this issue is Forum Lalu Lintas dan Angkutan Jalan (LLAJ).There are obstacles or constraints of Forum LLAJ in coordinating in handling transportation throughout the Province of Riau, among others have not integrity task execution to tackle illegal transportation, which often happens the leak information about the raid, the implementation of the joint chiefs are not routin, which provides a specific obliteration protection so the process of the impeccable can be difficult, terminal in shadow that can raise and lower the passenger so that the legal terminal become less work, the lack of awareness of the society even if it already knows the danger of using illegal transportation.The concept of the theory that is used by the researcher is coordination. Coordination consists of planning, communication, the division of task, and controling. This study uses qualitative research methods, with studies in descriptive data. In collecting of data, researcher’s using the technique of the interview, observation, the study of the literature and documentation, by using the key informant and late informants as a supplementary source of information.The result of this research show that the coordinating haven’t maximally between related instance (Forum LLAJ) in tackle illegal transportation in riau province. This is caused the status of the that institution is similar. That can be seen from the indicators of coordination, that is planning, communication, the division of tasks, controlling has not been categorized as a good coordination.Keywords : Coordination, Organization, Illegal Transportation